Bismuthoxyiodide Nanoflakes/Titania Nanotubes Arrayed p-n Heterojunction and Its Application for Photoelectrochemical Bioanalysis - Zhao, Wei-Wei (Nature Publishing Group, 2014)
We have developed sensitive detection of cancer biomarker vascular endothelial growth factor (VEGF) using the p-n heterojunction comprised of p-type BiOI nanoflakes (NFs) array and n-type TiO(2) nanotubes (NTs) array. Due to the unique arrayed structure and the synergy effect of photoelectrochemistry in the formed p-n junction, the synthesized configuration has superior excitation efficiency and thus excellent photoresponsibility. Then, the fabricated p-n heterojunction was integrated with an exquisite bioassay protocol for addressing VEGF using a sandwich immunoassay with glucosedehydrogenase (GDH) as the enzyme tags. Due to the excellent performance of BiOI NFs array/TiO(2) NTs array and the ingenious signaling mechanism, the proposed system could achieve the sensitive and specific VEGF detection. This work not only presents a simple BiOI NFs array/TiO(2) NTs array p-n heterojunction for general applications in the broad photochemistry areas, but also opens a different horizon for current development of advanced PEC biomolecular detection.